Ethics in medicine - Zaidi, Shabih H. (Springer International Publishing, 2014)
Medical ethics and the medical profession are inseparable, yet the formal teaching of medical ethics is a relatively new phenomenon. Furthermore, since the introduction of managed health care, with the physician becoming a 'health provider' and the patient a 'client', the whole concept of medical ethics has undergone a sea change. The contractual relationship between the provider and the client engenders caution and precaution, resulting in defensive medicine. This book both presents a succinct history of medical ethics and discusses a wide range of important ethical dilemmas in the provision of modern health care. A synopsis is provided of ethics through the ages and the role of ethics in the evolution of medicine. Principles and sources of medical ethics, as well as different religious and secular perspectives, are explained. Ethical concerns in relation to a variety of specific issues are then examined. These issues include, for example, human experimentation, stem cell research, assisted reproductive technologies, termination of pregnancy, rationing of health care, euthanasia, and quality of life issues. The author's many years of practicing medicine in different cultures and countries and his passion for religious works, philosophy, literature, poetry, history, and anthropology have informed and enriched the contents of this stimulating book.